Synthesis And Complexation Study Of The Conformational Isomer Of Cyclotetrachromotropylene - Abdullah, Ainnie Rahayu (2004)
Chromotropic acid reacts with formaldehyde to give the boat and chair conformers (25a and 25b respectively) of cyclotetrachromotropylene, 25, under different reaction conditions. At room temperature, 25b was isolated in which upon heating can convert to the thermodynamically more stable 25a. Conformer 25a is best synthesized via reflux in high yield (~ 90 %). In contrast, 25b can only be synthesized at room temperature giving a moderate yield of 20-25 %.